Development of Partial Discharge Detection Device for PD Detection on Medium Voltage XLPE Cable - Mohamad Radzi, M.I.F.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Partial Discharge (PD) is a natural phenomenon that occurs inevitably in high voltage equipment mainly due to the degradation of insulation materials. PD emits high frequency signals above 40 kHz which can be easily detected by Acoustic Emission (AE) method. This paper presents the processes of designing a PD detection device using ultrasonic sensor. The finished design is known as Partial Discharge Detection (PDD) device and its function is to detect PD on a medium voltage cross-linked polyethylene (XLPE) cable. Outcomes of the design processes show the complete design of the PDD device, the fabricated PDD device, and the functionality of the PDD device. The end results show that the PDD device is capable to detect PD much like a HFCT sensor does. The prototype device will be very beneficial in the upcoming future as the physical dimension of the device itself is relatively small, portable and cost efficient to manufacture when compared to the commercial PD sensing devices. Further advancement of the PD device, such as to incorporate Artificial Intelligence (AI), can be an added feature to the device moving forward. In addition, the prototype can also be converted into Flexible Printed Circuit Board (FPCB) form factor for ease of implementation and robustness. Such finding will be of utmost help to the power industries in monitoring PD activities on high voltage equipments using an affordable and efficient device in an effort to reduce the repair and maintenance costs. Â© 2021 IEEE.